Experimental and numerical investigation of the influence of rolling-induced sheet metal deformation on SPR joints - Schlichter, Malte Christian; Harabati, Özcan; Ludwig, Jean-Patrick; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
In the development of advanced lightweight automotive solutions, self-piercing riveting (SPR) offers the possibility of joining multi-material structures to fulfil a wide variety of requirements. With regard to the entire process chain, production-related pre-deformations of the parts to be joined can influence the geometric shape and load capacity of SPR joints. Various studies have investigated the influence of pre-stretched sheet materials, in the sense of pre-drawing processes, on the formation of SPR joints. The impact of pre-stretching sheet metals on the formation of their geometrical characteristics and the shear-tensile strength of SPR processes was observed [1]. Pre-rolled semi-finished products are also joined together in mixed material automotive structures, e.g. tailor rolled blanks. This work aims to investigate the influence of pre-rolled joining parts on the geometric formation and load-carrying capacity of SPR joints. For this purpose, sheets of metal are cold-formed using a rolling process to induce a defined strain-hardening state in the material and then joined in various combinations. As the degree of deformation increases, the rolling of samples can lead to minimal accumulation of damage in the sheet materials, which can influence the joint behaviour. The rolling process, as well as the subsequent joining process, are also investigated by FEM. The influence of pre-rolled semi-finished products on the strength of the SPR joints is investigated.

Investigation on manufacturing-induced pre-deformation on the fatigue behaviour of clinched joints - Schlichter, Malte Christian; Harabati, Özcan; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
The present study is an experimental analysis of the influence of pre-forming on the failure behaviour of clinched specimens under quasi-static and cyclic loading conditions. In this context, the geometric formation of the clinched joints is taken into account, with regard to the loading behaviour. The study also includes a comparison of the failure behaviour of quasi-static and cyclic tested specimen. Testing is done on non-pre-deformed and pre-deformed specimens. For this purpose, experimental investigations are carried out on two material combinations consisting of HCT590X steel sheet and EN AW-6014 T4 aluminium sheet. The focus is on the fatigue analysis of the clinched joints. The aim is to identify the failure modes under cyclic loading and the crack formation with regard to forming operations prior to the joining process. The investigations show that the cyclic load-bearing behaviour of the HCT590X joints is reduced by introducing a plastic pre-deformation of the to be joined parts.

High-cycle fatigue testing and parameter identification for numerical simulation of aluminum alloy EN AW-6014 - Chen, Chin; Schlichter, Malte Christian; Harzheim, Sven; Hofmann, Martin; Bobbert, Mathias; Meschut, Gerson; Wallmersperger, Thomas (Materials Research Proceedings)
Abstract. As a widely used sheet metal in clinched joints within the automotive industry, the aluminum alloy EN AW-6014 has been the focus of numerous studies. High-cycle fatigue (HCF) is a critical aspect when assessing the durability of clinched joints. In the present work, the HCF behavior of EN AW-6014 T4 was explored both experimentally and numerically. To model the fatigue behavior, Lemaitre’s two-scale damage model was used. Two key parameters, damage strength and damage exponent, are necessary for numerical investigations of HCF behavior. These parameters were determined through experiments with flat specimens and subsequently validated within a numerical model of clinched joints. The numerical results for fatigue match the experimental ones of the clinched joints quite well.

Simulation of the joining process of graded hardened multi-range capable rivets - Holtkamp, Pia Katharina; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
The versatile self-pierce riveting (V-SPR) is a further development of semi-tubular self-pierce riveting. V-SPR enables adaptation to changing boundary conditions, such as a change in the material thickness combination, without varying the rivet die combination due to increased punch actuation and the use of multi-range capable rivets [1]. The inner punch first sets the rivet. The outer punch then forms the rivet head to the respective sheet thickness. For this, the rivet requires a hard shank and a ductile rivet head, which is achieved by an inductive local hardening process [2]. Until now, the joint formation of rivets with graded hardness profile has been challenging to estimate in the FEM simulation due to the inhomogeneous material conditions in the rivet. In this study, a method capable of reproducing the experimentally determined hardness levels of rivets in detail is shown. This FE model enables the realistic modelling of the mechanical properties of the rivet on the basis of the hardness profile in order to predict the correct deformation processes and stresses during the riveting process. First, the detailed experimental hardness mapping of the locally heat-treated rivets is transferred into the FE model. The FEM material model can predict the local strength of the rivet based on hardness by scaling the flow curves. To estimate the predictive capability of the FEM model, the joint formation of rivets with different graded hardness profiles is compared experimentally and simulative. Based on the validated model, the influence of different rivet hardness profiles on the joint formation is analysed numerically. By adapting the material model, a high level of correlation between the experiment's joint formation and the simulation can be achieved.

Methodenentwicklung zur numerischen Auslegung von Klebverbindungen mit lackierten Fügeteilen - Hofmann, Julia; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Failure behavior prediction for resistance spot-welded three-layered dissimilar joints with advanced high-strength steel - Olfert, Viktoria; Bähr, Philipp; Schuster, Lilia; Westhoff, Julia; Yang, Keke; Ibeski, Enes; Hein, David; Sommer, Silke; Meschut, Gerson (Journal of Manufacturing Processes)

Testing, modelling and parameter identification for adhesively bonded joints under the combined influence of temperature and strain rate - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik (Journal of Adhesion Science and Technology)

From simulation to metamodel to experiment: Evaluating the prediction accuracy of polynomial regression models for clinch joint properties - Einwag, Jonathan-Markus; Steinfelder, Christian; Wartzack, Sandro; Brosius, Alexander; Goetz, Stefan (Journal of Manufacturing Processes)

Ressourceneffiziente Fertigung von Leichtbaustrukturen - Weck, Daniel; Müller-Pabel, Michael; Krampitz, Thomas; Hecker, Christine; Selvaggio, Alessandro; Gilich, Julian; Gude, Maik; Lieberwirth, Holger; Tekkaya, A. Erman; Meschut, Gerson (Werkstattstechnik online)
Zur Steigerung der Ressourceneffizienz technischer Komponenten sind neben dem Leichtbau insbesondere neuartige Fertigungstechnologien und Prozessketten mit geschlossenen Stoffkreisläufen von großer Bedeutung. Im Beitrag werden am Beispiel einer Demonstratorstruktur aus hybriden Leichtbauprofilen (Aluminium und faserverstärktes Polyamid) technisch-technologische Lösungsoptionen für die gesamte Prozesskette inklusive des Recyclings vorgestellt und in Pilotversuchen bewertet.

Solvolytically debondable adhesive systems – potentials and challenges for repair and recycling - Gilich, Julian; Kroos, Janika; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)
In the context of decarbonization initiatives, the repairability and recyclability of components have become a major concern in various industrial sectors, particularly for resource-intensive components. The development of innovative bonding and debonding processes that must adhere to the stringent mechanical specifications of the manufacturers and facilitate their efficient disassembly is a major issue faced in the implementation of a sustainable circular economy. Although adhesively bonded joints satisfy the stringent requirements for mechanical performance, they present several challenges during the repair and recycling process. Solvolytically debondable epoxy resin adhesives may be employed to overcome this issue. In this study, we aim to conduct an exploratory feasibility study on the application of such chemical debonding mechanisms within an adhesive bond as well as to systematically analyse and evaluate the suitability of such adhesive systems for various applications. To this end, we employed various thermo-analytical methods and quasi-static tensile tests to characterise the mechanical adhesive and joint properties of two solvolytically debondable adhesive systems. Furthermore, we analysed the debondability of the adhesive joints and evaluated their feasibility in an industrial environment. The results indicate considerable application potential for solvolytically debondable adhesives, along with further development steps currently required.

Influence of Liquid metal embrittlement on load-bearing capacity of resistance spot welds under crash loads: A study based on S-Rail components - Yang, Keke; Biegler, Max; Happe, Linus; Striewe, Marius; Olfert, Viktoria; Hein, David; Rethmeier, Michael; Meschut, Gerson (Materials Research Proceedings)
Abstract. Liquid Metal Embrittlement (LME) cracking is a well-documented issue encountered during resistance spot welding (RSW) of zinc-coated advanced high-strength steels (AHSS) in automotive manufacturing. Given that existing research has predominantly focused on laboratory-scale samples and lacks investigation into the load-bearing capacity of joints under crash conditions, this study aims to fill these gaps by analyzing third-generation zinc-coated AHSS. S-Rail components were produced through stamping to replicate real-world manufacturing conditions and geometries of automotive parts. To account for the disturbances typically encountered in production, samples with LME cracks were intentionally fabricated. Subsequently, a modified three-point bending test, assisted by numerical simulations, was developed to effectively apply loads to the weld spots of the S-Rail components. Results from crash tests demonstrated that observed light crack severity does not significantly compromise the joint's load-bearing capacity or lead to earlier joint failure.

Analysis of fatigue behaviour of self-piercing riveted joints under cyclic loading using laser vibrometry - Olfert, Viktoria; Yang, Keke; Gollnick, Maik; Krause, Jacob; Hein, David; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the field of online condition monitoring, non-destructive testing methods using active acoustic testing [1] emerged as innovative tools. These techniques are particularly effective because damage in joined structures leads to significant changes in their vibrational characteristics. However, the consistent use of online condition monitoring through active acoustic testing combined with complex pattern recognition for early crack detection in joined components has not yet been fully established. This research aims to develop an online crack detection system employing pattern recognition techniques under cyclic loading during fatigue tests, utilizing non-contact active acoustic testing with laser vibrometry. Due to the wide range of materials that can be joined, mechanical joining processes can be used in many different industry branches. Self-pierce riveting (SPR), in particular, is a well-established joining process. Therefore, the investigations for online crack detection initially focus on SPR joints. To achieve this, the fatigue behavior of SPR joints in a lap-shear configuration was characterized. Experimental fatigue testing demonstrated that SPR joint failure occurs either through cracks propagating in the sheet material away from the rivet or in the rivet foot, depending on the material combination. Laser vibrometry has been successfully used as a crack detection system and has proven to be effective in detecting crack initiation in SPR joints. Cracks can be detected without contact regardless of the material combination, the damage location, the size of the damage, or the type of damage. The optimization of the crack detection system involved several key enhancements, including adjusting data acquisition to improve crack detection, incorporating principal component analysis (PCA) to reduce dimensionality, and implementing a classification model based on a global training dataset. An intuitive, problem-specific software demonstrator for analyzing the crack initiation behavior of SPR joints under cyclic loading was developed and iteratively optimized. Future work will focus on the implementation of an autoencoder network to further enhance crack detection capabilities.

Comparison of the economic efficiency and sustainability of two debonding processes for structurally bonded sills - Jordan, Alex; Hermelingmeier, Lucas; Gilich, Julian; Meschut, Gerson; De Santis, Marco Sebastian; Schlüter, Alexander (Journal of Advanced Joining Processes)
In light of growing demands for resource efficiency and sustainability in vehicle engineering, the environmentally compatible separation of structural adhesive joints is gaining increasing relevance. This study presents a comparative analysis of two physically based debonding methods: the established hot-air process and a cryogenic cold process based on liquid nitrogen (LN2). The primary objective is to assess the ecological impact and process-related sustainability of both approaches. Experimental investigations were conducted on a component-representative triple-sheet structure that simulates common automotive flange joints. Thermal input was applied either by convective heating using a hot air gun or by direct cooling through a contact-based LN2 tool. The resulting temperature profiles were recorded using spatially distributed thermocouples. Subsequently, the outer panel was selectively debonded to replicate a repair scenario, and the mechanical integrity of the remaining adhesive joint was evaluated through Mode I testing of L-shaped specimens. Process data served as input for an Life Cycle Assessment (LCA) according to DIN EN ISO 14040. The cryogenic method achieved a 40% reduction in carbon footprint compared to the hot-air process (0.337 kg vs. 0.559 kg CO2-equivalents), primarily due to its shorter process time and more efficient heat transfer. While the hot-air method’s impact is mainly driven by electrical energy use, that of the cold method stems from cryogenic media consumption. Notwithstanding certain disadvantages in specific impact categories, the LN2-based process exhibits a superior overall ecological performance and signifies a promising solution for repair- and recycling-oriented adhesive separation in structural vehicle applications.
Keywords: Sustainable debonding; Structural adhesives; Sustainable joining technologies; Life Cycle Assessment (LCA); Automotive repair process; Economically efficient debonding

A novel welding schedule for expanding the expulsion-free process window in resistance spot welding of dissimilar joints with ultra-high strength steel - Yang, Keke; Wang, Zhuoqun; Haak, Viktor; Olfert, Viktoria; El-Sari, Bassel; Hein, David; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing Processes)

Einfluss von Schweißparametern und Montageverfahren auf die elektrische Kontaktgüte von Aluminium-Massebolzen - Haak, Viktor; Yang, Keke; Meschut, Gerson (Schweißen und Schneiden)
Ein wichtiger Bestandteil jeder Fahrzeugkarosserie sind Massebolzen, die zur Herstellung der elektrischen Schnittstelle zwischen der leitfähigen Karosserie und dem Bordnetz dienen. Eine zuverlässige Signal- und Leistungsübertragung erfor-dert minimale Übergangswiderstände an den elektrischen Anschlusspunkten des Massebolzensystems und muss ver-schiedenen Betriebs- und Umweltbedingungen über die gesamte Lebensdauer standhalten. Der Übergangswiderstand wird von mehreren Faktoren beeinflusst (z. B. Verbindungsgeometrie, Kontaktkraft, Temperatur, Werkstoff) und erhöht sich im Laufe der Betriebszeit infolge unterschiedlicher Alterungsmechanismen. Dieser Beitrag befasst sich mit der elektrischen Charakterisierung von Massebolzen aus AlMg5 mit einer ZnNi-beschichteten Stahl-Hutmutter auf einem AlMg3-Blech. Es werden ausgewählte fertigungs-, montage- und betriebsbedingte Einflussgrößen auf den elektrischen Verbindungs-widerstand analysiert. Als wirtschaftliche und etablierte Fügetechnologie kommt das Lichtbogenbolzenschweißen mit Hubzündung zum Einsatz. Zur Herstellung qualitativ hochwertiger Schweißverbindungen wird mittels einer statistischen Versuchsplanung ein geeigneter Referenzparametersatz ermittelt. Weiterhin wird der montagebedingte Einfluss anhand des Mutter-Anziehmoments bei der Kabelschuhmontage auf den elektrischen Verbindungswiderstand untersucht. Zusätzlich werden die Strombelastbarkeit und der maximal zulässige Betriebsbereich des Massebolzensystems ermittelt.

Integration of multiple-linear and tumbling kinematics into self-piercing riveting - Holtkamp, Pia Katharina; Wituschek, Simon; Lechner, Michael; Meschut, Gerson (MATEC Web of Conferences)
Conventional mechanical joining processes are typically rigid in their tool systems and can only react to changing process and disturbance variables to a limited extent. At the same time, various industries are increasingly trending towards multi-material systems consisting of parts with varying geometric and mechanical properties. Due to the varying properties, rigid mechanical joining processes require sampling procedures and periodic changes of tool components or auxiliary joining parts. Consequently, research is focusing on versatile mechanical joining processes that allow increased control by modifying the process parameters. Two processes based on self-piercing riveting can achieve a significant increase in process influence possibilities through a multi-linear actuator as versatile self-piercing riveting (V-SPR) and a tumbling superimposed actuator as tumbling self-piercing riveting (T-SPR). Initial research into V-SPR has shown that this process can be used to achieve a higher variation in overall package thickness by adapting the rivet geometry and using multiple linear actuators. The T-SPR process also enables increased material flow control by means of targeted compression of the rivet using the tumbling actuator, thereby extending the range of joints that can be manufactured. Based on these two processes, a combination of the two mechanisms of action is to be developed.

Non-destructive testing in versatile joining processes - Lechner, M.; Borgert, Thomas; Busch, Matthias; Harms, A.; Holtkamp, Pia Katharina; Römisch, D.; Wituschek, Simon; Kappe, Fabian (Materials Research Proceedings)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT's application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysis.

Occurrence and avoidance of liquid metal embrittlement in resistance spot welding of springback-afflicted deep-drawn components - Biegler, Max; Yang, Keke; Meschut, Gerson; Rethmeier, Michael (Science and Technology of Welding and Joining)
This study investigates the occurrence and mitigation of liquid metal embrittlement occurring during resistance spot welding in deep-drawn automotive components, specifically focusing on an S-Rail made from advanced high-strength steel. A simulation-based liquid metal embrittlement risk criterion based on local major component stresses was established and used to quantify and compare liquid metal embrittlement risks between different tests. Experimental and numerical analyses were conducted, revealing that springback significantly impacts liquid metal embrittlement formation. Adjustments in electrode geometry and hold time post-welding were found to mitigate liquid metal embrittlement risks. The effects of stack-up configuration and related parameter settings on liquid metal embrittlement occurrence were identified and liquid metal embrittlement was effectively prevented across both stack-up configurations. These findings advance the understanding of liquid metal embrittlement mechanisms and provide practical approaches to enhance the spot weld quality in AHSS-based body-in-whites.

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Analysis of the binding mechanisms depending on versatile process variants of self-piercing riveting - Lüder, Stephan; Holtkamp, Pia Katharina; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson; Lechner, Michael; Schmale, Hans Christian (Materials Research Proceedings)
The constantly increasing demand for climate protection and resource conservation requires innovative and versatile joining processes that improve adaptability to the joining task and robustness to enable flexible manufacturing on a production line. Therefore, the versatile SPR (V-SPR) and tumbling SPR (T-SPR) were developed. Using the example of a mixed material combination HCT590X+Z (t0 = 1.0 mm) / EN AW-6014 T4 (t0 = 2.0 mm), these processes were examined and compared with regard to the binding mechanisms form closure and force closure using micrographs, non-destructive resistance measurements and destructive torsion tests. For this purpose, a new sample geometry was defined, and the methods were adapted to the SPR process variants.
Keywords: Joining; Self-Piercing Riveting; Sheet Metal